SETPOINT OPTIMIZATION FOR THE CONTROL SYSTEM OF THE MOTOR GRADER IN HEAVYLOAD MODE - V. A. Meshcheryakov; V. V. Weber (Вестник СибАДИ)
Introduction. The authors suggest the optimal tuning method foran automatic control system of the heavy motor grader blade. The demonstrated system regulates the value of digging force. Moreover, the setpoint optimization criterion is the maximum of production rate.Materials and methods. The optimal setpoint is generating to the signal estimations, specifically to the measured digging force and the wheels slip ratio during the previous stroke of the motor grader.There searchincludes:development of the blade control system functional diagram including the setpoint former;meaningful estimation of the slip ratio signal for control purposes;development of the setpoint forming algorithm for a microprocessor control unit;program realization of the motor grader workflow model and simulation;development of the algorithm to compose the lookup table containing optimal setpoint values and based on simulation results;dependence of optimal setpoint on the incoming signal estimations.Results. The lookup table of optimal setpoint values is obtained, the estimations of digging force and wheels slip ratio are presented. In addition, the authors suggest the control system structure with the optimal setpoint former and also develop the former operation algorithm.Discussion and conclusion. The optimal setpoint values are theoretically validated for the motor grader control system. The tuning method for an automatic control system of the heavy motor grader blade has the following characteristics as:the optimal control criterion as the production rate;process dynamics and stochastics;the excessive slippage time ratio.